2018
DOI: 10.1126/scirobotics.aat4440
|View full text |Cite
|
Sign up to set email alerts
|

Biohybrid robot powered by an antagonistic pair of skeletal muscle tissues

Abstract: Biohybrid robots are attracting attention as promising candidates to enhance robot applicability to studies on biological designs and in vitro construction of biological dynamic systems. Rapid progress in biohybrid robots with skeletal muscle tissues formed on a flexible substrate has enabled various types of locomotion powered by muscle tissue. However, it has been difficult to achieve high levels of both large and long-term actuations of the skeletal muscle tissues because of their spontaneous shrinkage thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
231
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(237 citation statements)
references
References 32 publications
4
231
0
2
Order By: Relevance
“…Such robot was composed of a 3D‐printed resin skeleton bearing electrodes for the active stimulation of myoblast‐laden hydrogel sheets, which were mounted on two sides of the skeleton to act as antagonist muscles (Figure b). The authors showed that the biohybrid robot was capable of large movements (rotation angle of the joint was close to 90°) that can be used to perform simple actions (e.g., grabbing and transporting small objects) . Furthermore, they showed that the hybrid robot was successfully actuated over a long period of time (≈1 week).…”
Section: Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Such robot was composed of a 3D‐printed resin skeleton bearing electrodes for the active stimulation of myoblast‐laden hydrogel sheets, which were mounted on two sides of the skeleton to act as antagonist muscles (Figure b). The authors showed that the biohybrid robot was capable of large movements (rotation angle of the joint was close to 90°) that can be used to perform simple actions (e.g., grabbing and transporting small objects) . Furthermore, they showed that the hybrid robot was successfully actuated over a long period of time (≈1 week).…”
Section: Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
“…b) Biohybrid robot powered by an antagonistic pair of skeletal muscle tissues. Adapted with permission . Copyright 2018, American Association for the Advancement of Science.…”
Section: Skeletal Muscle Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Following, there are less-concrete distinctions among modes of (non-)aliveness compared to our traditional understandings of those states (Jipson & Gelman, 2007). For instance, biohybrid robots combine organic components (like cultured muscle tissues) with machine components (like gels, electrodes, and metal frameworks) so that electrical stimulation allows the robot to perform humanlike behaviors like joint movement (see Morimoto, Onoe, & Takeuchi, 2018). Hence, when a biohybrid robot moves a hand or a finger, is that agent somehow alive?…”
Section: Ontological Shiftsmentioning
confidence: 99%
“…Hydrogels are crosslinked polymer networks with very high water content, biocompatibility, and fascinating stimuli‐responsive properties, and are promising for applications in tissue engineering, soft actuators, controlled drug release, and so on. However, conventional hydrogels usually exhibit poor mechanical strength and low stretchability, due to the lack of efficient energy dissipation mechanisms .…”
Section: Introductionmentioning
confidence: 99%